ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA MATERI PECAHAN KELAS V SDN 06 SANGGAU - Eka Prastiwi; Risdiana Andika Fatmawati; Muhammad Aqmal Nurcahyo (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2022)
The purpose of this study was to describe the types of errors and to identify the number of students who made each type of error in solving math problems with fractions. This research is a descriptive qualitative research by using a checklist sheet instrument. Researcher in this study collected the data with documents. The main data sources used in this study were 25th grade students and the answers of fifth grade students for the 2020/2021 academic year. The results showed that there were four types of errors made by students, namely conceptual errors, operating errors, careless errors, and notation errors. Based on the results of the analysis conducted by the researcher, as many as 18 of 25 students or 72% of students made operational errors,  17 of 25 students or 68% of students made conceptual errors, 4 of 25 students or 16% of students made careless errors, and 25 students or 16% of students made notational errors in solving math problems with addition and subtraction operations on fractions with different denominators.